Association of oral glucose tolerance test and pregnancy and fetal outcome - Bhagavan, Veena K. R.; Shetty, Seemitha; Rao, Aadhishree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Gestational diabetes mellitus (GDM) affects 2-25% of pregnancies depending on population characteristics and criteria used. It is associated with an increased risk of fetal malformation and perinatal mortality. The aim of the study was to know the prevalence of GDM, the risk factors associated with women with GDM and the feto-maternal outcome. Methods: A prospective study conducted among 200 antenatal women attending Obstetrics and Gynaecology (OBG) Outpatient Department in A. J. Institute of Medical Sciences and Research Center from March 2019 to August 2019. GDM was diagnosed with 2-hour 75 gm oral glucose tolerance test according to diabetes in pregnancy study group of India (DIPSI) criteria. Basic demographic details and maternal and fetal outcomes were analysed. Results: The prevalence of GDM was high (24.5%) compared to other studies. Normoglycemia was achieved with diet alone in 71.5%, diet and metformin in 16.3% and 12.2% with insulin. Risk factors included higher body mass index (BMI) and history of GDM. Emergency caesarean rate was higher among GDM women (p<0.05). Fetal complications and neonatal intensive care unit (NICU) admissions were also higher in this group (p<0.001 and p<0.05). Conclusions: The higher prevalence shows the importance of early detection and timely intervention for pregnancy complicated with GDM. Due to this high-risk pregnancy, there’s increased incidence of maternal and fetal outcomes which can be reduced with glycaemic control and adequate fetal surveillance.